PD-L1 regulates tumorigenesis and autophagy of ovarian cancer by activating mTORC signaling - Gao, Hongmin (Biosci Rep, 2019)
PD-L1 is a well-known immune co-stimulatory molecule that regulates tumour cell escape from immunity by suppressing the immune response. However, the clinical significance of PD-L1 in the progression of ovarian cancer is unclear. Our study demonstrated that PD-L1 is up-regulated in ovarian tumour tissue compared with its expression level in adjacent normal tissue. Furthermore, we confirmed that PD-L1 increases the proliferation of cancer cells by activating the AKT-mTORC signalling pathway, which is also enhanced by the expression of S6K, the substrate of mTORC. In addition, PD-L1 promotes the autophagy of ovarian cancer cells by up-regulating the expression of BECN1, a crucial molecule involved in the regulation of autophagy. In conclusion, PD-L1 may provide a target for the development of a novel strategy for the treatment of ovarian cancer.